PATTERN OF CARCINOMA OF ORAL CAVITY REPORTING AT DENTAL DEPARTMENT OF AYUB MEDICAL COLLEGE - Wahid, Abdul; Ahmad, Sajjad; Sajjad, Mohammad (Journal of Ayub Medical College Abbottabad, 2005)
Background: Carcinoma of oral cavity is amongst the first ten commonest malignancies in Pakistan. Districts of Hazara (NWFP) and Northern Areas of Pakistan are among the high risk areas. Here we present a report of oral cancers received in this center over a period of 10 years. Methods: This clinicopathological study consists of cases of carcinoma of oral cavity presenting to dentistry department of Ayub Medical College Abbottabad during 1993-2003. All cases were clinically examined and provisionally diagnosed. Biopsy was taken from all the lesions and the tissues submitted to histopathology department of Ayub Medical College. Results: There were 50 carcinoma cases in the study, including 30 (60%) males and 20 (40%) females. Among these, 47 (94 %) were diagnosed as squamous cell carcinomas, that consisted 30 (63.82 %) males and 17 (36.17%) females. The other 6 % lesions were histologically diagnosed as malignant melanoma, adenocarcinoma and acinar cell carcinoma. The age of squamous cell carcinoma cases was 41-71 years. The maximum number of squamous cell carcinomas (34%) effected buccal mucosa. The other common sites were lip (26%), tongue (21%) and gums (19%). Conclusion: The results of this study are comparable with other such studies done in Pakistan and else where in the world showing commonality of factors associated with the development of the disease in this region of the country, which necessitates a detailed prospective study. Keywords: Oral carcinoma, Squamous cell carcinoma, smokeless tobacco